PURIFICATION AND IN VITRO ANTIOXIDANT ACTIVITY OF POLYSACCHARIDE ISOLATED FROM GREEN SEAWEED CAULERPA RACEMOSA - S. MAHENDRAN; S.SARAVANAN (International Journal of Pharma and Bio Sciences, 2013)
The present investigation was to study the purification and In vitro antioxidant activities of the polysaccharide from green seaweedCaulerpa racemosa. The polysaccharide was isolated and purified from green seaweed C. racemosa by ethanol precipitation and DEAE-cellulose ion exchange chromatography. The chemical analysis of polysaccharide showed carbohydrate content (47.43%), sulfate content (12.86%) and uronic acid content (4.9%). The In vitro antioxidant activity was determined by free radical scavenging assays such as total antioxidant activity (80.24±0.56%), Reducing power assay [(0.243±0.04) - (1.624±0.07)],Hydrogen peroxide assays (77.22±0.67%),DPPH assays (71.42±0.74%), ABTS assays(73.32±1.27%), Hydroxyl assays (68.29±1.03), Superoxide anion assays (66.17±0.77 %) and Nitric oxide radical assay (40.64±1.82%). The antioxidant capacities of the C. racemosa polysaccharides showed potential rich sources of natural antioxidants.